Rational design of a ratiometric two-photon fluorescent probe for real-time visualization of apoptosis. Issue 74 (30th August 2018) - Huang, Yinliang; Zhou, Qin; Feng, Yan; Zhang, Wan; Fang, Guoshun; Fang, Min; Chen, Man; Xu, Changzhi; Meng, Xiangming
Abstract : A ratiometric two-photon fluorescent probe (Mito-DCHO ) was rationally designed for real-time assessing and dual-color visualization of the early stage of apoptosis. Abstract : A dialdehyde-functionalized ratiometric two-photon fluorescent probe (Mito-DCHO ) based on a symmetric carbazole-containing two-dimensional ICT system was rationally designed for cysteine-specific detection in mitochondria, which was utilized for real-time assessing and dual-channel visualization of the early stage of apoptosis by monitoring mitochondrial oxidative stress levels.